2006
DOI: 10.1111/j.1365-3059.2006.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen, phosphorus, potassium and calcium nutrition on strawberry anthracnose

Abstract: The effects of a range of concentrations of four nutrients -nitrogen, phosphorus, potassium and calcium -in fertilizer solutions on the severity of anthracnose on strawberry cv. Nyoho cultivated under a noncirculation hydroponics system were determined after inoculation with Colletotrichum gloeosporioides . Crop growth and tissue nitrogen, phosphorus, potassium and calcium contents of the entire above-ground parts of the plant were also investigated. Elevated nitrogen and potassium concentrations in the fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 14 publications
(19 reference statements)
0
32
1
4
Order By: Relevance
“…These results agree with those observed by Pereira et al (2012), who applied increasing doses of N and K and did not observe significant effect of the fertilizers on the variable mean fruit mass of blackberry plants. In strawberry, Nam et al (2006) showed a positive relation between N and K in the increment of dry matter; however, these authors warn about the unbalanced use, which can pose risk of diseases like anthracnose. These authors recommend low contents of these elements in the plant.…”
Section: Resultsmentioning
confidence: 97%
“…These results agree with those observed by Pereira et al (2012), who applied increasing doses of N and K and did not observe significant effect of the fertilizers on the variable mean fruit mass of blackberry plants. In strawberry, Nam et al (2006) showed a positive relation between N and K in the increment of dry matter; however, these authors warn about the unbalanced use, which can pose risk of diseases like anthracnose. These authors recommend low contents of these elements in the plant.…”
Section: Resultsmentioning
confidence: 97%
“…Excess of potassium, 30 mmol L -1 , also influenced increase of anthracnose (Colletotrichum gloeosporioides) in strawberries (Nam et al, 2006). Potassium applied appropriately in soil, 8%…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is not a rule, however, as some studies report increased disease with increasing concentration of K, such as in the cases of Cercospora coffeicola in coffee and Colletotrichum gloeosporioides in strawberry, due to an imbalance of K and Ca (Garcia Júnior et al, 2003;Pozza et al, 2001;Nam et al, 2006). Potassium participates in regulating various physiological pathways, such as enzyme activation, protein synthesis, photosynthesis, osmoregulation, transport, and stress resistance (Marschner, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of K on disease incidence could be affected by the amount and source of this element, plant and pathogen species and trial type (Wang et al 2013). For example, Nam et al (2006) found that strawberries that were grown with excess K were very susceptible to infection by Colletotrichum gloeosporioides, but host resistance was greatly enhanced when no K was supplied. This result was observed because the dose proximal to optimal plant K status induced the synthesis of molecules including reactive oxygen species (ROS) and phytohormones such as auxin, ethylene and jasmonic acid (Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%